Role of cytology and immunochemistry in diagnosis of metastatic malignancies in the lung: A critical appraisal. Issue 11 (24th October 2018) - Manucha, Varsha; Hansen, Jeffery T.; Gonzalez, Maria F.; Akhtar, Israh
Abstract : Background: Lung is one of the most common sites for primary and metastatic malignancies and a challenging site to diagnose primary versus a metastatic origin of the tumor on cytology. Pathologic diagnosis of the site of origin of cancer has major implications in the management and staging purposes and may have to be followed by testing for predictive/prognostic markers. The clinical history of a known extrapulmonary primary and the radiologic findings of multiple nodules in the lung are useful in arriving at the right diagnosis but is not always available. Rarely pulmonary metastasis may be the first manifestation of an extrapulmonary tumor or may even present as a single nodule. Method: In this study, we reviewed cytomorphologic features of tumors metastatic to the lung (2014‐2017) in conjunction with immunochemistry and evaluation of needle core biopsy when available. The review of the slides was performed with an emphasis on our ability to identify the site of origin in the tumors. Results: We identified 47 cases of metastatic tumors in the lung diagnosed on cytology. Clinical history was available in 83% cases and with aid of immunostains, a definitive diagnosis on the origin of the tumor was made in all these cases. In the remaining 8 cases, a primary origin could only be suggested. The use of immunochemistry facilitated the diagnosis but could be misleading. Conclusion: The approach to the diagnosis of metastatic tumors in the lung on cytology should be largely guided by the previous clinical history and comparison with previous tissue/cellular material if available.